English Language Acquisition in Deaf Learners with Hearing Parents and Hearing Learners with Deaf Parents - Muhammad Arkan Dafi; Muhammad Khairan; Ananda Ajeng; Najwa Najwa; Erly Mulfias Yuli; Fatima Kamila (Foremost Journal, 2026)
Early language access plays a decisive role in shaping communicative competence and motivational dispositions in English as a Foreign Language (EFL) learning. Within deaf education contexts, differences in linguistic environments often result in unequal opportunities to develop confidence and willingness to engage in communication. Framed by Surdo-glottodidactics, this paper offers a qualitative documentary-based comparative analysis of deaf learners with hearing parents and hearing learners who are Children of Deaf Adults (CODAs). Drawing on interdisciplinary literature in deaf studies, bilingualism, and second language acquisition, the analysis highlights how parental support interacts with the timing and accessibility of language exposure to influence learners? Willingness to Communicate (WTC). The findings suggest that early and visually accessible language input, particularly sign language during the first six months of life, provides a crucial linguistic foundation for deaf learners. In contrast, CODAs benefit from a ?bimodal advantage? through continuous exposure to both signed and spoken languages, fostering higher communicative confidence. This study concludes that parental facilitation as a primary catalyst for communicative success and ensuring coordination between home and school is crucial to sustain consistent vocabulary exposure.